Luminescence of doped CdS nanocrystals: effect of doping and capping agent - Hasanzadeh, J.; Farjami Shayesteh, S. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Cu and Fe doped cadmium sulfide nanoparticles were prepared with a wet chemical synthesis by mixing the reactants in double distilled water solvent. Thioglycerol (TG) was employed as the capping agent and also the reaction catalyst. The estimated particle size of prepared samples was found in the range 3–4 nm. Properties of particles were investigated using photoluminescence spectroscopy (PL) and X-ray diffraction analysis (XRD). XRD pattern of samples reveals a hexagonal crystal structure at room temperature. We have studied effect of doping and TG concentration on the luminescence of doped CdS nanocrystals. There is a noticeable increase of the PL intensity when TG concentration increased. The PL spectra include two bands, due to emission of traps and surface state.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 921-928
Keywords: optyka; nanoparticles; doping; luminescence; crystal structure; capping agent